A model-based technique to identify lubrication condition of hydrodynamic bearings using the rotor vibrational response. (August 2021) - Oliveira, Marcus Vinícius Medeiros; Cunha, Barbara Zaparoli; Daniel, Gregory Bregion
Abstract: Faults related to hydrodynamic bearing can imply in high maintenance costs when late-detected and lead to system shutdown. Thus, techniques of early fault diagnosis have high relevance to the reliability of rotating machinery. However, a common fault caused by inadequate bearing oil supply has not yet received appropriate attention. This paper presents a new approach to model and identify oil supply in hydrodynamic bearings. The developed identification technique is a model-based process that uses the rotor vibration to access the bearing lubrication. Numerical identifications were performed and the results showed that the proposed method satisfactorily estimates the oil flowrate in bearings under starved and flooded lubrication conditions, representing a useful and promising tool for fault diagnosis applied to rotating machinery. Highlights: A new approach to model different bearing lubrication conditions was developed. The directional response of the rotor is sensitive to the oil supply flowrate. Promising identification of oil supply flowrate for starved and flooded conditions. A suitable alternative to detect oil starvation fault in the bearing.